Phase I feasibility study for intrathecal administration of trastuzumab in patients with HER2 positive breast carcinomatous meningitis. (May 2018) - Bonneau, Claire; Paintaud, Gilles; Trédan, Olivier; Dubot, Coraline; Desvignes, Céline; Dieras, Véronique; Taillibert, Sophie; Tresca, Patricia; Turbiez, Isabelle; Li, Jacques; Passot, Christophe; Mefti, Fawzia; et al.
Abstract: Purpose: Leptomeningeal carcinomatosis (MC) is commonly associated with HER2-positive breast cancer (HER2-BC), with a poor prognosis and no standardised treatment. We conducted a phase I dose-escalation study of intrathecal (IT) administration of trastuzumab in HER2-BC patients with MC to determine the maximum tolerated dose (MTD), which was based on both the achievement of a trastuzumab intra-cerebrospinal fluid concentration close to a conventional therapeutic plasma concentration (30 mg/L) and/or dose-limiting toxicity (DLT). Methods: The protocol planned IT administration of trastuzumab (30 mg, 60 mg, 100 mg or 150 mg dose levels) once a week, over the course of at least 4 weeks. Sixteen patients with MC from HER2-BC received IT trastuzumab. Intra-cerebrospinal fluid samples were obtained before each injection for pharmacokinetics. Results: We did not observe DLT of IT trastuzumab. Eleven patients had no toxicity attributed to IT trastuzumab. For 60 mg or higher dose levels, minor toxicities attributed to IT trastuzumab included headache (2 patients), nausea (2 patients), vomiting (1 patient), cervical pain (1 patient) and peripheral neuropathy (1 patient). Two patients experienced immediate toxicity including headache or vomiting. The mean residual intra-cerebrospinal fluid concentration of trastuzumab was 27.9 mg/L for the 150 mg dose level. Three patients achieved a clinical response, seven patients had stable disease and four patients had progressive disease. Conclusions: The MTD and recommended phase II weekly dose of IT trastuzumab in patients with HER2-BC and MC is 150 mg. A phase II trial using this dose regimen in MC from HER2-BC is ongoing. Registration identification: ClinicalTrials.gov Identifier:NCT01373710 (https://clinicaltrials.gov/ct2/show/NCT01373710?term=trastuzumab+intrathecal&rank=1 ). Highlights: First phase I study for intrathecal injection of trastuzumab for breast cancer patients with carcinomatous meningitis. No dose-limiting toxicities occurred. Clinical response or stable disease was observed. The maximum tolerated dose and recommended weekly dose of intrathecal trastuzumab is 150 mg. A phase II trial using this dose regimen in leptomeningeal carcinomatosis from HER2 breast cancer is ongoing.